Students’ independent learning implementation during learning from home period (a study at Unika Santu Paulus Ruteng, Flores) - Gabriel Fredi Daar (Politeknik Negeri Bali, 2020)
This study explored students’ independent learning during the Learning from Home Period within this covid 19 outbreak. This study was conducted at the Faculty of Health Science and Agriculture Unika Santu Paulus Ruteng, Flores covering four study majors. In order to obtain the objective of the research, it’s used qualitative studies with a phenomenological approach. Data were obtained through interviews. For the purpose of individual interviews, it’s chosen 12 respondents consisting of 8 students and 4 teachers taken purposively. The research results showed that 1) Students use books, modules, portable computers, and mobile phones as the media to apply independent learning. Certain teachers use online applications such as Goggle Classroom, Email, Whats app, and websites to engage students with internet learning instruments. Dealing with learning sources, students use files in the form of PPT, PDF, a word containing the materials, learning videos, notes, google, youtube, assignments distributed by teachers, and some other materials gained by the students themselves from the internet. 2) Students haven’t possessed time management skills. They don’t provide a specific time to learn the materials they obtain from teachers. They only used the learning schedule provided by the campus. 3) Teachers play most of their roles as instructors and facilitators. As instructors, teachers provided some instructions through materials or subject matters to be learned by the students. Moreover, students are asked or instructed to complete certain assignments within the time limit set up through the learning application used. Meanwhile, as facilitators, teachers provided opportunities for the students to discuss and ask questions through an online application provided. Even, certain questions asked through WhatsApp answered directly by the teachers. 4) There are some advantages and obstacles that could be the policymakers and school authority concerns in order to promote optimal self-learning during this covid-19 outbreak.